The Evolutionary emergence of language : social function and the origins of linguistic form - Knight, Chris, 1942-; Studdert-Kennedy, Michael; Hurford, James R. (Cambridge University Press, 2000)
This book covers the origins and early evolution of language. Its main purpose is to synthesize current thinking on this topic, particularly from a standpoint in theoretical linguistics. It is suitable for students and scholars of human evolution, evolutionary psychology, linguistic anthropology, and general linguistics. It includes contributions from many of the best-known figures in this field.